Further Results on Total Edge-Vertex Domination - Abdulgani Şahin (Journal of Mathematics)
Total edge-vertex domination is a new total domination-type parameter. In this paper, the author shows that determining the total edge-vertex domination number in bipartite planar graphs is NP-complete. Also, the author obtains a structural relation between total domination number and total edge-vertex domination number and characterizes the trees whose total edge-vertex domination number is equal to total domination number.